The Left-Right Symmetry Breaking Mechanism for the New Left-Right Symmetry Model - Akmal Ferdiyan; Apriadi Salim Adam; Mirza Satriawan (JPSE (Journal of Physical Science and Engineering), 2020)
We added a mechanism for breaking the left-right (LR) symmetry in the new variant of the left-right symmetry model. We added to the modela new scalar field ϕ that transforms oddly under the new LR transformation. The mechanism can provide different values for the vacuum expectation values of the left and right Higgs scalar, νL, and νR. A simple numerical analysis was performed to make sure that the parameters space in this model can satisfy some constraints of the model. It is shown that for some parameter values, this mechanism can fulfill the constraint of νL= 246 GeV and the ratio νR⁄νL >30. DOI: http://dx.doi.org/10.17977/um024v5i12020p001